The Strategies To Increase The Interest In Reading Literacy In Islamic Education And Moral Character In The Era Of Globalization - Akbar Setiadi, Fauzan; Wildan Shohib, Muhammad (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
This research aims to explore strategies and methods that are more effective and efficient in improving the quality of literacy, interest in reading about Islamic Religious Education and Akhlakul Kharimah that must be instilled, especially among junior high school students in facing the challenges of globalization and digitalization today. The results of the research conducted have indicated that the explanation of strategies that focus on active student involvement in discussions, the use of information and communication technology, on the use as a source of literacy reading material is more effective and relevant to the needs and interests of students in order to improve the quality of literacy in reading Islamic Religious Education books and Akhlakul Kharimah. The results of these findings can create a very important combination in efforts to improve the quality of Islamic Religious Education and the formation of good attitudes for students in the Era of Globalization, by fostering interest in reading literacy so that there is more interest in the basic foundation for understanding and training efforts in creating good Islamic values in everyday life. and create an effective and efficient learning environment for students.